ANALISIS BALANCED SCORECARD SEBAGAI SARANA PENGUKURAN KINERJA PERUSAHAAN (Studi Kasus pada Pabrik Gula Pesantren Baru Kediri) - Ami Dhatul Solichah (Jurnal Administrasi Bisnis, 2015)
Measurement of the performance of a company adapted to the conditions and forms of enterprise. Measurements should be able to see all sides of a part, both in terms of customers, in financial terms, in terms of production and in terms of employees. Measurement of performance through strategic management approach is summarized in a strategic measurement Balanced Scorecard. Balanced Scorecard measure performance through four perspectives, such us financial perspective, customer perspective, internal business process and learning and growth perspective. Measurement of performance against PG Pesantren approach the decree of the Minister of State-Owned Enterprises No. Kep-100/MBU/2002 to assess the soundness of state-owned enterprises. Results stated that the company's performance during the year 2011-2013 in financial terms with healthy predicate "AAA" for the years 2011-2012, as well as healthy "AA" for the year 2013. However, for non-financial perspective is still in fairly good condition, look at the level of each customer the declining and fluctuating levels of employee productivity. Keyword: Perspectives of Balanced Scorecard, Assess the Soundness of State-Owned Enterprises Abstrak: Pengukuran kinerja sebuah perusahaan disesuaikan dengan kondisi dan bentuk perusahaan. Pengukuran seharusnya dapat melihat dari semua sisi bagian, baik segi pelanggan, segi keuangan, segi produksi maupun segi karyawan. Pengukuran kinerja melalui pendekatan manajemen strategis terangkum dalam suatu pengukuran strategis Balanced Scorecard. Balanced Scorecard mengukur kinerja melalui empat perspektif yaitu perspektif keuangan, perspektif pelanggan, perspektif proses bisnis internal maupun perspektif pertumbuhan dan pembelajaran. Pengukuran kinerja terhadap PG Pesantren menggunakan pendekatan Keputusan Menteri BUMN No: Kep-100/MBU/2002 untuk menilai kesehatan BUMN. Hasil menyatakan bahwa kinerja perusahaan selama tahun 2011-2013 dalam segi keuangan dengan predikat sehat “AAA” untuk tahun 2011-2012, serta sehat “AA” untuk tahun 2013. Namun untuk perspektif non finansial masih dalam kondisi cukup baik, melihat tingkat pelanggan yang tiap tahun menurun dan tingkat produktivitas karyawan yang fluktuatif. Kata Kunci: Perspektif Balanced Scorecard, Menilai Kesehatan BUMN